2019
DOI: 10.3390/su11246934
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Tourism: A Competitiveness Strategy Perspective in Baja California

Abstract: Sustainability plays an important role in society by improving long-term quality of life, including future generations, seeking harmony between economic growth, social development and the protection of the environment. For decades, companies focused their efforts on maximizing returns for their stakeholders, setting aside the preservation of the environment by making indiscriminate use of local resources, which had a direct impact on the social and economic well-being of it, however today the organizations ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 3 publications
(2 reference statements)
1
15
0
1
Order By: Relevance
“…Ideally, tourism sustainable competitiveness should capture price competitiveness, government cohesion and international openness (Escoto, Boza, & Madrigal, 2019;Khalifa, 2020). Purchasing power parity reflects differences in the cost of goods and services in the country, tax payments are those profits (Mendola & Volo, 2017) which are imposed on tourists, and transportation costs required to be undertaken (Khan, Bibi, Lorenzo, Lyu, & Babar, 2020;Zhao, Li, & Yu, 2017).…”
Section: Policy and Regulatory Environmentmentioning
confidence: 99%
“…Ideally, tourism sustainable competitiveness should capture price competitiveness, government cohesion and international openness (Escoto, Boza, & Madrigal, 2019;Khalifa, 2020). Purchasing power parity reflects differences in the cost of goods and services in the country, tax payments are those profits (Mendola & Volo, 2017) which are imposed on tourists, and transportation costs required to be undertaken (Khan, Bibi, Lorenzo, Lyu, & Babar, 2020;Zhao, Li, & Yu, 2017).…”
Section: Policy and Regulatory Environmentmentioning
confidence: 99%
“…Tourism is an entire system of its own, characterized as complex and dynamic, necessitating the need for sustainability considerations [15]. Sustainability plays an important role in society by improving long-term quality of life, including future generations, seeking harmony between economic growth, social development and the protection of the environment [16]. Accommodation providers such as hotels, campsites, and holiday villages can use ecolabels to show their green credentials to potential customers [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sustainability plays an important role in society by improving long-term quality of life, including future generations, seeking harmony between economic growth, social development, and the protection of the environment [16]. It was shown that tourism is menacing not only the vitality of their local economies, but also the integrity of their heritage and the quality of life of their residents.…”
Section: The National Composition Of Foreign Tourists Accommodated In the Czech Republicmentioning
confidence: 99%
“…However, the area of land suitable for agricultural use is still declining in the Czech Republic. Escoto et al draw attention to the interdisciplinary character of sustainability: "sustainability plays an important role in society by improving long-term quality of life, including future generations, seeking harmony between economic growth, social development and the protection of the environment" [2]. "Modern agriculture and modern small-peasant production have different requirements for agriculture sustainability" [3].…”
Section: Introductionmentioning
confidence: 99%